2022
DOI: 10.3389/fchem.2021.812375
|View full text |Cite
|
Sign up to set email alerts
|

Pd Doped Co3O4 Loaded on Carbon Nanofibers as Highly Efficient Free-Standing Electrocatalyst for Oxygen Reduction and Oxygen Evolution Reactions

Abstract: Self-supporting electrodes usually show excellent electrocatalytic performance which does not require coating steps, additional polymer binders, and conductive additives. Rapid in situ growth of highly active ingredient on self-supporting electric conductors is identified as a straight forward path to prepare binder-free and integrated electrodes. Here, Pd-doped Co3O4 loaded on carbon nanofiber materials through electrospinning and heat treatment was efficiently synthesized, and used as a free-standing electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…20 Several metals are used to modify the Co 3 O 4 nanoparticles including Fe, Mn, Cu, Ni, Mo, 20,21 Ag, and Pd. 22,23 Jincy and Meena synthesized copper-doped cobalt oxide nanoparticles by a hydrothermal method and they observed that these nanoparticles exhibited extreme sensitivity towards NH 3 gas at room temperature even at a lower concentration of 5 ppm in comparison to undoped Co 3 O 4 . 24 In another work, Cu-doped Co 3 O 4 nanosheets obtained by a solvothermal method show enhanced electrochemical performance due to the reduced particle size and larger surface area.…”
Section: Introductionmentioning
confidence: 99%
“…20 Several metals are used to modify the Co 3 O 4 nanoparticles including Fe, Mn, Cu, Ni, Mo, 20,21 Ag, and Pd. 22,23 Jincy and Meena synthesized copper-doped cobalt oxide nanoparticles by a hydrothermal method and they observed that these nanoparticles exhibited extreme sensitivity towards NH 3 gas at room temperature even at a lower concentration of 5 ppm in comparison to undoped Co 3 O 4 . 24 In another work, Cu-doped Co 3 O 4 nanosheets obtained by a solvothermal method show enhanced electrochemical performance due to the reduced particle size and larger surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Weng and coworkers fabricated Pd-doped Co 3 O 4 anchored on carbon nanofiber as a bifunctional catalyst for the OER and oxygen reduction reaction (ORR). 31 Wei et al developed Ir-doped Co 3 O 4 with a low Ir loading of 2.88 wt% for efficient acidic OER. 32 Despite the progress, most of the previously reported heterometal-doped Co 3 O 4 displayed unsatisfactory HER electrocatalytic activity in comparison with Pt-based electrocatalysts, which becomes a major concern for alkaline OWS.…”
Section: Introductionmentioning
confidence: 99%